Diversity and drivers of arbuscular mycorrhizal fungi in the rhizosphere soil of wine grape in the eastern foot of Helan Mountain in Ningxia of China - Zhang, Qiangqiang; Ma, Siyuan; Wang, Ruotong; Li, Ling; Zhang, Qingchen; Ju, Mingxiu; Gu, Peiwen (Frontiers in Microbiology, 2025)
IntroductionArbuscular mycorrhizal fungi (AMF) are symbiotic microorganisms that exert positive effects on their host plants. However, their colonization and community diversity in wine grapes remain unclear.MethodsThis study investigated roots and rhizosphere soils from Cabernet Sauvignon grapevines in vineyards in seven ecological regions at the eastern foot of the Helan Mountains in Ningxia, China. We employed Illumina MiSeq high-throughput sequencing to analyze AMF community composition and diversity in the rhizosphere soil, and examined the effects of soil factors on AMF communities.ResultsThe results showed that the grapevine root system was colonized by AMF, with significant spatial heterogeneity in colonization rates and spore densities across the sample plots. Differences in the diversity of the AMF communities in the rhizosphere soil of wine grapes in the different sample plots were observed, and these AMF communities were further divided into three groups. In total, 168 operational taxonomic units were detected in the rhizosphere soil, corresponding to 40 AMF species from five orders, seven families, and seven genera. The Glomus and Glomus melanosporum were the dominant genus and species, respectively. Claroideoglomus and Glomus were identified as biomarkers. Soil pH and organic matter were key factors influencing AMF colonization, abundance, diversity, and community composition.DiscussionThe grape rhizosphere in this region hosts a rich diversity of AMF. This finding provides a reference for the protection and commercial cultivation of AMF in wine grape rhizospheres.